2021
DOI: 10.1158/2159-8290.cd-20-1285
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Spatial and Cellular Architecture of Lung Adenocarcinoma by Multiregion Single-Cell Sequencing

Abstract: Little is known of the geospatial architecture of individual cell populations in lung adenocarcinoma (LUAD) evolution. Here, we perform single-cell RNA sequencing of 186,916 cells from five early-stage LUADs and 14 multiregion normal lung tissues of defined spatial proximities from the tumors. We show that cellular lineages, states, and transcriptomic features geospatially evolve across normal regions to LUADs. LUADs also exhibit pronounced intratumor cell heterogeneity within single sites and transcriptional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(129 citation statements)
references
References 47 publications
14
113
1
1
Order By: Relevance
“…Our data, in consensus with the existing literature, suggested an increase in basal and aberrant basaloid cells in the distal lung epithelium of IPF patients, which have been in the past identified by their cytokeratin 5 (CK5, the protein product of KRT5 mRNA) intracellular or NGFR cell surface expression 50 . First, we determined by flow cytometry the expression of the CK5 protein in the epithelial compartment of six donor and six IPF lungs.…”
Section: Basal Cell Markers Expression In Donor and Ipf Lungsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data, in consensus with the existing literature, suggested an increase in basal and aberrant basaloid cells in the distal lung epithelium of IPF patients, which have been in the past identified by their cytokeratin 5 (CK5, the protein product of KRT5 mRNA) intracellular or NGFR cell surface expression 50 . First, we determined by flow cytometry the expression of the CK5 protein in the epithelial compartment of six donor and six IPF lungs.…”
Section: Basal Cell Markers Expression In Donor and Ipf Lungsupporting
confidence: 91%
“…We further confirm by flow cytometry and immunofluorescence analysis the CK5 pos cell expansion in IPF, and show that CK5 and NGFR expression define two distinct basal cell populations with differential behavior in IPF. The increased expression in IPF of CD24, a cell surface marker known to be highly expressed in cancer cells 50 and aberrant epithelial cells in IPF 30,31 , is also confirmed, offering a potential cell surface marker to sub-type together with Lysotracker incorporation various populations of epithelial cells in donor and IPF lung.…”
Section: Discussionmentioning
confidence: 65%
“…ScRNA-seq analysis of 10 normal lung tissues and 10 fresh LUAD tissues found that the TME was composed of cancer-associated myofibroblasts, exhausted CD8 + T cells, proinflammatory monocyte-derived macrophages, plasmacytoid dendritic cells, myeloid dendritic cells, anti-inflammatory monocyte-derived macrophages, normal-like myofibroblasts, NK cells, and conventional T cells ( 69 ). Multi-region of five early-stage LUADs and 14 multi-region normal lung tissues found that the Treg + cells are increased in normal tissues with proximity to LUAD and the signatures and fractions of cytotoxic CD8+ T cells, antigen-presenting macrophages, and inflammatory dendritic cells were decreased ( 37 ).…”
Section: Application Of Single-cell Technologies In the Early Stage Of Lung Cancermentioning
confidence: 99%
“…Therapeutic vaccines activate the T cell to recognize cancerous neoantigens, initiating an immune response for individualized vaccination ( 7 ). Therefore, LUAD requires combined therapy and we should classify the LUAD population with different molecular characteristics ( 8 ).…”
Section: Introductionmentioning
confidence: 99%